Contextos familiares comunitarios y el aprendizaje en el Subnivel de Educación Inicial I en el sector Chambapongo cantón Salcedo. - Miniguano Miniguano, Joffre Neptalí (2021)
This research was focused on the study of the community family context and its incidence in learning in the sub-level of Initial Education I of the Chambapongo sector in the Salcedo canton. The problem addressed lies in the deficiencies or risk factors of the family community context for children's learning. The methodology used in the project was of a mixed approach, feasible project modality, type of applied research, the research level was conceptual, apprehensive, comprehensive and integrative. The techniques used were the observation of the infants, the interview with the coordinator and the survey of the parents, with their respective instruments. With this, it was possible to show that in the sector there are risk factors such as the low level of schooling of families, the lack of accessibility to basic services, the lack of knowledge and application of early stimulation techniques, among others. For this reason, a proposal of ten workshops was designed through which parents were oriented, orienting them about techniques and activities to affectively stimulate children's learning. This proposal was validated through the critical judgment of three experts and three users, obtaining a favorable endorsement that supports the viability, feasibility and contribution of the proposal.